Tick-Borne Encephalitis Serological Survey of Students from University of Liège - Saegerman, Claude; Wielick, Constance; Darcis, Gilles; Maréchal, Nicole; Bureau, Fabrice; Gillet, Laurent; Donneau, Anne-Françoise; Ariën, Kevin K.; Van Esbroeck, Marjan (Viruses, 2025)
Background: Zoonotic risks in exposed students are poorly documented in Belgium. According to the literature, even though human tick-borne encephalitis (TBE) infection risk has increased significantly in southern Belgium, no previous human serological survey has demonstrated specific antibodies directed at TBE virus. Methods and principal findings: The aim of this paper was to perform a representative serological survey on sera involving students at the University of Liege, in the southern part of Belgium, to discover possible exposure to TBEV. A total of 207 sera samples were randomly chosen and analyzed using ELISA IgM (with 1 positive student out of 207) and ELISA IgG (with 10 positive students out of 207), subsequent serial immunofluorescence antibody testing (IFAT) IgG (with 8 positive students out of 10 positive in ELISA IgG) and serial IFAT IgM (with 1 negative student out of 1 positive in ELISA IgM), and confirmatory tests, i.e., 50% and 90% plaque reduction neutralization tests (PRNTs) (1 strongly positive student out of 8 positive in IFAT). Conclusions and significance: The exposure of students from the southern part of Belgium (area with increasing risk) to TBEV was assessed for the first time. Antibodies against TBEV could only be demonstrated in 1 out of 207 students. This finding contributes to better decision-making in public health and prevention and management of tick-borne diseases in the context of climate change. Awareness among all students should be prioritized, with prevention measures against tick bites, particularly during forest and recreational activities contributing to risk, to maintain the current low seroprevalence levels.